Eugenol derivatives prospectively inhibit l-asparaginase: A heady target protein of Salmonella typhimurium. (January 2018) - Vimal, Archana; Jha, Anubhuti; Kumar, Awanish
Abstract: Salmonella typhimurium is the causative agent of severe human infections and mortality throughout the world. Pacing advent of new resistance mechanisms in this microorganism exists, rendering treatment of infectious disease difficult. Ciprofloxacin is no longer considered the first choice of antimicrobial agent due to the emergence of resistance. Therefore, the need for scenario is to find out novel drug target and its potential inhibitor to fight against this pathogen. The present study was undertaken to find out a novel drug target and its inhibitor for improving the current therapeutic methods for treating Salmonella infections. It is found thatl -asparaginase is exploited by the pathogen for its survival benefit. Therefore, it could be targeted to fight against lethality caused by Salmonella infections. In the present in silico study, the 3-D structure of the enzymel -asparaginase was modelled by using homology modeling technique. Thereafter, molecular docking studies and ADMET prediction to assess pharmacokinetic profiles of test ligands (eugenol and its derivative) was performed. The results show that eugenol and its derivative are capable of inhibiting the Salmonella virulent proteinl -asparaginase. There were 18 ligands including ciprofloxacin (used as reference) were docked. The lowest binding energy was observed with eugenol derivative 8 i.e −5.836 kcal/mol while for ciprofloxacin was −4.661 kcal/mol. The docking of the eugenol derivative 8 withl -asparaginase revealed a strong interaction between them with two hydrogen bonds. Thr 35 and Asp 116 residues are actively participating in this interaction. The result of ADMET profiling suggests the potency of eugenol and its derivatives against Salmonella l -asparaginase-II as a compelling drug candidate. These findings provide useful information on the biological role, structure-based drug design and potent inhibitor ofl -asparaginase for the development of effective therapeutic molecule against Salmonella infection. Highlights: Drug-resistant Salmonella typhimurium is a severe threat to human health worldwide. In silico approach was used to control virulence via targetingl -asparaginase. l -asparaginase- a novel drug target was inhibited by eugenol and its derivatives. Thr 35 & Asp 116 residues are majorly involved in the binding site interaction. In silico ADMET study suggests that pharmacokinetic properties are within range.